Implementasi Sistem Informasi Penghitung Berat Badan Ideal Balita (SIPEBABA) berbasis Website dengan Waterfall - Sara, Putu Agisna Fransisco; I Ketut Rama Pradipta; Bella Yasinta Usman (Universitas Dinamika, 2025)
The growth and development of toddlers is a very important thing for parents to pay attention to. One thing that needs to be considered is the toddler's weight. Toddler weight is an anthropometric measure used to detect growth rate and nutritional status. Posyandu is a party that plays an active role in handling toddlers starting from checking their weight, giving vaccinations, and regular visits. Posyandu XYZ is one of the Posyandu that has implemented technology in the form of a website. However, the website has not been implemented optimally for posyandu services because it cannot be used to facilitate the implementation of services for toddlers and the elderly. In this research, a website-based application for calculating the ideal weight of toddlers was designed using the Laravel framework and the Waterfall method. This research produces a website-based information system for calculating the ideal weight of toddlers (SIPEBABA) and tested using SUS with a score of 77.90. This application can be used by Posyandu XYZ to maximize the efficiency of their employees' work.